Inhibition of sonic hedgehog pathway and pluripotency maintaining factors regulate human pancreatic cancer stem cell characteristics - Tang, Su-Ni; Fu, Junsheng; Nall, Dara; Rodova, Mariana; Shankar, Sharmila; Srivastava, Rakesh K. (International journal of cancer, 2012)
Activation of the sonic hedgehog (SHh) pathway is required for the growth of numerous tissues and organs and recent evidence indicates that this pathway is often recruited to stimulate growth of cancer stem cells (CSCs) and to orchestrate the reprogramming of cancer cells via epithelial mesenchymal transition (EMT). The objectives of this study were to examine the molecular mechanisms by which (‐)‐epigallocatechin‐3‐gallate (EGCG), an active compound in green tea, inhibits self‐renewal capacity of pancreatic CSCs and synergizes with quercetin, a major polyphenol and flavonoid commonly detected in many fruits and vegetables. Our data demonstrated that EGCG inhibited the expression of pluripotency maintaining transcription factors (Nanog, c‐Myc and Oct‐4) and self‐renewal capacity of pancreatic CSCs. Inhibition of Nanog by shRNA enhanced the inhibitory effects of EGCG on self‐renewal capacity of CSCs. EGCG inhibited cell proliferation and induced apoptosis by inhibiting the expression of Bcl‐2 and XIAP and activating caspase‐3. Interestingly, EGCG also inhibited the components of SHh pathway (smoothened, patched, Gli1 and Gli2) and Gli transcriptional activity. Furthermore, EGCG inhibited EMT by inhibiting the expression of Snail, Slug and ZEB1, and TCF/LEF transcriptional activity, which correlated with significantly reduced CSC's migration and invasion, suggesting the blockade of signaling involved in early metastasis. Furthermore, combination of quercetin with EGCG had synergistic inhibitory effects on self‐renewal capacity of CSCs through attenuation of TCF/LEF and Gli activities. Since aberrant SHh signaling occurs in pancreatic tumorigenesis, therapeutics that target SHh pathway may improve the outcomes of patients with pancreatic cancer by targeting CSCs.